A prominent air pollutant, Indeno[1,2,3-cd]pyrene, enhances allergic lung inflammation via aryl hydrocarbon receptor - Tzu-Hsuan Wong (Nature Portfolio, 2018)
Abstract Chronic exposure to ambient polycyclic aromatic hydrocarbons (PAHs) is associated with asthma, but its regulatory mechanisms remain incompletely defined. We report herein that elevated levels of urinary 1-hydroxypyrene, a biomarker of PAH exposure, were found in asthmatic subjects (n = 39) as compared to those in healthy subjects (n = 43) living in an industrial city of Taiwan, where indeno[1,2,3-cd]pyrene (IP) was found to be a prominent PAH associated with ambient PM2.5. In a mouse model, intranasal exposure of mice with varying doses of IP significantly enhanced antigen-induced allergic inflammation, including increased airway eosinophilia, Th2 cytokines, including IL-4 and IL-5, as well as antigen-specific IgE level, which was absent in dendritic cell (DC)-specific aryl hydrocarbon receptor (AhR)-null mice. Mechanistically, IP treatment significantly altered DC’s function, including increased level of pro-inflammatory IL-6 and decreased generation of anti-inflammatory IL-10. The IP’s effect was lost in DCs from mice carrying an AhR-mutant allele. Taken together, these results suggest that chronic exposure to environmental PAHs may pose a significant risk for asthma, in which IP, a prominent ambient PAH in Taiwan, was shown to enhance the severity of allergic lung inflammation in mice through, at least in part, its ability in modulating DC’s function in an AhR-dependent manner.